Multiplex Three-Dimensional Brain Gene Expression Mapping in a Mouse Model of Parkinson's Disease - Brown, Vanessa M. (Cold Spring Harbor Laboratory Press, 2002)
To facilitate high-throughput 3D imaging of brain gene expression, a new method called voxelation has been developed. Spatially registered voxels (cubes) are analyzed, resulting in multiple volumetric maps of gene expression analogous to the images reconstructed in biomedical imaging systems. Using microarrays, 40 voxel images for 9000 genes were acquired from brains of both normal mice and mice in which a pharmacological model of Parkinson's disease (PD) had been induced by methamphetamine. Quality-control analyses established the reproducibility of the voxelation procedure. The investigation revealed a common network of coregulated genes shared between the normal and PD brain, and allowed identification of putative control regions responsible for these networks. In addition, genes involved in cell/cell interactions were found to be prominently regulated in the PD brains. Finally, singular value decomposition (SVD), a mathematical method used to provide parsimonious explanations of complex data sets, identified gene vectors and their corresponding images that distinguished between normal and PD brain structures, most pertinently the striatum. [All study results and supplementary data are available on the web at http://www.pharmacology.ucla.edu/smithlab/genome_multiplex and at http://www.genome.org. Microarray data are also available at GEO, http://www.ncbi.nlm.nih.gov/geo, under the series accession no. GSE30.]